Isolation and identification mould micoflora inhabiting plant leaf litter from Mount Lawu, Surakarta, Central Java - MUHAMMAD ILYAS (Biodiversitas Journal of Biological Diversity, 2007)
A study on isolation and identification mould inhabiting plant leaf litter had been conducted. The objective of the study was to isolate and identify mould inhabiting plant leaf litter from Mount Lawu, Surakarta, Central Java. The mould isolation was based on washing and filtering with membrane isolation method. The result showed that 39 moulds generas with 55 species varians, one group identified in class level, and three groups of unidentified mould isolates had been isolated. Taxas distributions showed that there were endophyte and phytopatogen mould isolates had been isolated such as Fusarium, Pestalotiopsis, Phoma, and Coelomycetes. However, typical soil taxa and common saprobic fungi such as Aspergillus, Cunninghamella, Mucor, Paecilomyces, Penicillium, Rhizopus, and Trichoderma remain dominated the resulted isolates..Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: mould, leaf litter, Mount Lawu, washing and filter membrane isolation method